MEMBANGUN PENDIDIKAN KARAKTER GENERASI MUDA MELALUI BUDAYA KEARIFAN LOKAL DI ERA GLOBAL - Budiwibowo, Satrijo (Premiere Educandum, 2013)
The parameter of the nationâs achievement is that of youth in the future, because maintaining the achievement is usually more difficult than fighting for it. Youth are young generation who are ablidged to maintain leadership and struggle to stay fit around the stricker competition in all aspects due to the higher velocity of service capital throughout the world, which influence the national integrity of a nation. This can only be resolved by producing human resource with high competitive advantage. Globalization has become the term to call a world condition which takes place without boreder. The globalization progress has evidently stood aside local wisdoms of a nation. This article serves an aoutlook on the efforts of universal character building which is rooted from the local wisdom.Â Keywords: Character Education, Local WisdomÂ